The Structural Relationship Model of Product Quality, Brand Image, and Brand Equity toward Purchase Decisions of Imported Chinese Products of Bangkok Citizens - Joemsuwan, Chanwit; Boonyoo, Thanyanan (Ph.D. in Social Sciences Journal, 2024)
This research article aimed to study the structural relationship model of product quality, brand image, and brand equity toward purchase decisions of imported Chinese products of Bangkok citizens. This study was quantitative research. Samples in this study were 250 samples of Bangkok citizens purchasing imported Chinese products on the concept of Hair, Ringle, and Sarstedt (2011). These samples were selected by using accidental sampling. A questionnaire was implemented as a research tool in this study. Statistics used in this study were percentage, means, standard deviation, and Structural Equation Modelling program. Findings are as follows: (1) the product quality had a direct effect on brand equity and had an indirect effect on purchase decisions with the path coefficient scale at 0.388 and 0.194 respectively; however, the product quality had no direct effect on purchase decisions with the path coefficient scale at 0.129. (2) the brand image had a direct effect on brand equity and purchase decisions and had an indirect effect on purchase decisions as well. The path coefficient scales were at 0.533, 0.329, and 0.267 consecutively. And (3) the brand image directly affected purchase decisions with a path coefficient scale of 0.501.